1984
DOI: 10.1037/0735-7028.15.6.798
|View full text |Cite
|
Sign up to set email alerts
|

Practicing school psychologists: Their characteristics, activities, and populations served.

Abstract: In order to collect current information about school psychologists, a questionnaire was sent to a nationwide, random sample of practicing school psychologists. The responses of 877 school psychologists were analyzed. Results indicated the majority of time was spent in assessment (54%), followed by intervention (23%), consultation (19%), and research (/%). A reduction in assessment and increases in intervention, consultation, and research were desired. In addition, the responding school psychologists devoted 84… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
60
0

Year Published

1985
1985
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(64 citation statements)
references
References 9 publications
4
60
0
Order By: Relevance
“…As recently as the early 1980s, 54% of the field was reported to be male (Smith, 1984). However, gradual growth in the percent of females had begun years earlier, and by 1999 to 2000, women represented 70% of all school psychologists .…”
Section: Gendermentioning
confidence: 96%
See 3 more Smart Citations
“…As recently as the early 1980s, 54% of the field was reported to be male (Smith, 1984). However, gradual growth in the percent of females had begun years earlier, and by 1999 to 2000, women represented 70% of all school psychologists .…”
Section: Gendermentioning
confidence: 96%
“…For example, Smith (1984) reported that ratios of 1,500:1 or less were associated with more intervention-based services and less assessment services. Based on analyses of data for the 1994 to 1995 school year, found that higher ratios were associated with more initial specialeducation evaluations and reevaluations and a greater percentage of time spent overall in specialeducation-related activities.…”
Section: Students To School Psychologist Ratiomentioning
confidence: 96%
See 2 more Smart Citations
“…For example, practicing school psychologists have reported that consultation generally has been a high priority in their delivery of services (Smith, 1984). However, although many practitioners have received didactic training, very few training programs provide a field practicum or other supervised experience in consultation (Meyers, Wurtz, & Flanagan, 1981).…”
mentioning
confidence: 99%